Transancestral mapping and genetic load in systemic lupus erythematosus - Langefeld, Carl D.; Ainsworth, Hannah C.; Cunninghame Graham, Deborah S.; Kelly, Jennifer A.; Comeau, Mary E.; Marion, Miranda C.; Howard, Timothy D.; Ramos, Paula S.; Croker, Jennifer A.; Morris, David L.; Sandling, Johanna K.; Almlöf, Jonas Carlsson; et al. (Nature Publishing Group, 2017)
Systemic lupus erythematosus (SLE) is an autoimmune disease with marked gender and ethnic disparities. We report a large transancestral association study of SLE using Immunochip genotype data from 27,574 individuals of European (EA), African (AA) and Hispanic Amerindian (HA) ancestry. We identify 58 distinct non-HLA regions in EA, 9 in AA and 16 in HA (B50% of these regions have multiple independent associations); these include 24 novel SLE regions (Po5 10 8), reﬁned association signals in established regions, extended associations to additional ancestries, and a disentangled complex HLA multigenic effect. The risk allele count (genetic load) exhibits an accelerating pattern of SLE risk, leading us to posit a cumulative hit hypothesis for autoimmune disease. Comparing results across the three ancestries identiﬁes both ancestry-dependent and ancestry-independent contributions to SLE risk. Our results are consistent with the unique and complex histories of the populations sampled, and collectively help clarify the genetic architecture and ethnic disparities in SLE